Bactericidal/Permeability-Increasing Protein Is an Enhancer of Bacterial Lipoprotein Recognition - Bülow, Sigrid; Zeller, Lisa; Werner, Maren; Toelge, Martina; Holzinger, Jonas; Entzian, Clemens; Schubert, Thomas; Waldow, Franziska; Gisch, Nicolas; Hammerschmidt, Sven; Gessner, André (Frontiers in Immunology, 2018)
Adequate perception of immunologically important pathogen-associated molecular patterns like lipopolysaccharide and bacterial lipoproteins is essential for efficient innate and adaptive immune responses. In the context of Gram-negative infection, bactericidal/permeability-increasing protein (BPI) neutralizes endotoxic activity of lipopolysaccharides, and thus prohibits hyperactivation. So far, no immunological function of BPI has been described in Gram-positive infections. Here we show a significant elevation of BPI in Gram-positive meningitis and surprisingly a positive correlation between BPI and pro-inflammatory markers like TNF. To clarify the underlying mechanisms, we identify BPI ligands of Gram-positive origin, specifically bacterial lipopeptides and lipoteichoic acids, and determine essential structural motifs for this interaction. Importantly, the interaction of BPI with these newly defined ligands significantly enhances the immune response in peripheral blood mononuclear cells mediated by Gram-positive bacteria, and thereby ensures their sensitive perception. In conclusion, we define BPI as an immune enhancing pattern recognition molecule in Gram-positive infections.